The Growing Challenge of Dual Credit/Enrollment - Eric G Tenbus; Daniel Schierenbeck (Academic Chairpersons Conference Proceedings, 2017)
Face the dual credit challenge by taking back control of the program and strengthening it to ensure high academic standards. This presentation will explain the dual credit phenomenon and offer practical advice in countering it, navigating the political landmines, and making it work better for your department.
Keywords: Dual; Enrollment; Challenge; Gen Ed; Politics